Psychological assessment tool for patients diagnosed with absolute uterine factor infertility and planning to undergo uterine transplantation. (August 2014) - Saso, S.; Bracewell-Milnes, T.; Ismail, L.; Hamed, A. H.; Thum, M-Y.; Ghaem-Maghami, S.; Del Priore, G.; Smith, J. R.
Abstract Uterine transplantation (UTn) has been proposed as a treatment option for women diagnosed with absolute uterine factor infertility (AUFI) and who are willing to bear their own child. AUFI renders a woman 'unconditionally infertile'. For AUFI women in general, UTn may offer a way to re-discover their own femininity through the restoration of fertility. Thus, when faced with a patient who may undergo UTn, the 'holistic approach' takes on an extra meaning. This is because the psychological element is two-sided for these patients. On one side lies the psychology of infertility, and on the other and equally important, is the substantially higher prevalence of psychiatric disorders in transplant candidates and recipients than in the general population. However, the psychology of a potential recipient of a uterine graft in order to bring about fertility has not been adequately explored or reviewed scientifically. We have presented here an outline of the areas which should be included in a psychological assessment for patients wishing to undergo UTn.